P53 as an Adverse Prognostic Factor in Patients with Uterine Sarcoma: A Retrospective Study of 113 Patients - Yun Zhou; Lin-Jing Yuan; Ying Xiong; Xin Huang; Jia-xin Lin; Min Zheng (International Journal of Medical Research, 2014)
Objective: objective.Uterine sarcoma is an aggressive malignancy with poor prognosis. This study aimed to identify prognostic factors for this rare cancer. Methods: A retrospective study involved 113 patients with uterine sarcomas was performed, including 61 cases identified by systematic computer-based searches of the literature and 52 patients diagnosed with uterine sarcomas at the SYSUCC. Immunohistochemical analyses of p53, p27, CD146 and Ki-67 were performed in tissue samples collected from the 52 patients in this institution, and for p53 in 45 cases from the literature. Results: Median survival was 30.7 months for all 113 patients . The 5-year overall survival (OS) and disease-free survival (DFS) rates were 44% and 46%, respectively. Patient age, disease stage, histological type, tumor size and p53 were significant prognostic indicators for survival. Positive expression of p53 was significantly correlated with adverse OS, FIGO stage, premenopause, age <50 years, tumor size >5 cm, negative lymph node metastasis and negative expressions of p27 and CD146. Cox regression analysis showed that FIGO stage and p53 were independent prognostic factors for OS and DFS. Conclusions: Our results indicated that P53 is a potential, novel prognostic marker for patients with uterine sarcoma and serves to guide treatment strategies.